Reliance on multiple performance measures and manager performance - Mahfud Sholihin, Mahfud (Emerald Group Publising Limited, 2010)
Purpose – The performance measurement literature suggests that companies should consider increasing the diversity of their performance measures to embrace both financial and non-financial measures. The purpose of this paper is to examine whether the use of multiple performance measures which includes both financial and non-financial measures in evaluating subordinates’ performance (reliance on multiple performance measures (RMPM)) affects their performance, or whether the effect is contingent on the specificity and difficulty of the goals contained in the measures. Design/methodology/approach – A questionnaire survey to various functional managers within a single organization supported by interviews. Findings – The effect of RMPM on subordinate managers’ performance is contingent on goal specificity. However, the paper does not find the same results for goal difficulty. These findings are discussed within the context of the organization studied. Research limitations/implications – The samples are from a single organization. Further work would be needed to examine whether the results are generalizable into other organizations and/or settings. Practical implications – The paper provides insight on how performance measures used to evaluate managers should be designed. Originality/value – This paper contributes to the literature on supervisory evaluative style, performance measure diversity and goal-setting theory. Keywords Performance measures, Management effectiveness, Targets Paper type Research paper